Butterflies(Lepidoptera: Hopalcera)of Taman Negara Johor Endau Rompin,Johor - Maryati Mohamed,; Norradihah Ismaili ,; Mohd Zulfadhli Mohd Munjayen, (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
Taman Negara Johor Endau Rompin (TNJER) is an old tropical rainforest of the world, where the rocks had been dated to be at least 248 million years old. It is located in the southern part of Peninsular Malaysia, in the state of Johor. Studies on diversity of butterflies (Lepidoptera: Rhopalocera) of TNJER had been reported since 1987 with the latest report being published in 2005. A pioneering scientific expedition to TNJER was conducted in 1985-1986 and a total of 179 butterfly species recorded and reported in 1987. The second expedition in 2002-2003 reported 206 species of butterfly, published in 2005. Thereafter, collections of butterfly were carried out opportunistically employing two methods: manual collection using aerial net and baited traps using over- ripe banana. A grant from Universiti Tun Hussein Onn Malaysia enabled researchers to make several collection visits in 2013 (February, June and September). By the most recent study in 2013, 38 species had been added to the collection with 11 new records for TNJER. A more intensive collection is planned for 2014 to evaluate the actual butterfly diversity of an old tropical forest, using more quantitative method such as point counting. Perhaps when substantial reference collections had been gathered and checklist up-dated, the data of butterfly diversity could be compared between an old tropical forest (TNJER) and newer tropical forest of Borneo, particularly in Sabah and Sarawak to note differences if any occurred.